Evaluasi Program Hipertensi di Puskesmas Beutong Kabupaten Nagan Raya - Sari Wartini; Natha Bella; Putri Nur Ramadhani; Dharina Baharuddin; Asnawi Abdullah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Hypertension is a non-communicable disease that poses a major challenge to the health system, particularly in rural areas. Community health centers (Puskesmas), as first-level service facilities, play a crucial role in the early detection, control, and prevention of hypertension complications. However, the achievement of Minimum Service Standards (SPM) targets is often hampered by various factors. This study aims to evaluate the implementation of the hypertension prevention and control program at the Beutong Community Health Center, Nagan Raya Regency, and to identify supporting and inhibiting factors in achieving program targets. The study used a mixed methods approach with formative and summative evaluation designs. Quantitative data were collected through secondary documents, while qualitative data were obtained through field observations and in-depth interviews with health workers and cadres. The evaluation was conducted using an input–process–output–outcome approach. Data analysis was descriptive and thematic with source triangulation to enhance validity. The evaluation results indicate that from the input side, the availability of tools and human resources is still limited, especially in Posbindu activities. In terms of process, screening and education are ongoing but not evenly distributed across all work areas. From the output side, the coverage of hypertension case examinations and detection has not yet reached the SPM target. The outcomes indicate that patient adherence to treatment and healthy lifestyle changes still need to be improved. The main inhibiting factors include lack of community participation, limited facilities, and suboptimal recording and reporting. The hypertension program at the Beutong Community Health Center (Puskesmas) has been running but is not yet optimal. Strengthening logistics, information systems, empowering cadres, and improving community education are needed to support the achievement of Minimum Service Standards (SPM) and reduce the number of complications caused by hypertension.